Mechanical characteristics of rice seedlings under wind stress - Li, Lianhao; Qin, Weihua; Xu, Lianchao; Zhu, Chenhui; Liu, Bingxu (International Journal of Agricultural and Biological Engineering, 2025)
Machine transplanting, as an advanced production technology, is widely used for rice cultivation. However, the transplanted rice seedlings may float over and die under the stress of external force in extreme windy weather. In order to reveal the mechanism of floating rice seedlings, it is vital to investigate their force characteristics. In this study, steady-state simulations of the flow around the rice seedlings are conducted. It is found that the drag force of rice seedlings is generated by the positive pressure of the windward side and the negative pressure of the leeward side. Both the drag force and the moment are proportional to the square of wind speed, regardless of the wind direction angle or the inclined angle of rice seedlings. The drag force coefficient exhibits a complex pattern with the wind direction angle, but decreases as the inclined angle increases. The moment arm of the drag force initially increases and then decreases with increasing wind direction angles, while it decreases with larger inclined angles. It indicates that the variation in wind direction angle may increase the risk of lodging in rice seedlings, whereas the inclined angle does not have such an effect. The results of this study provide a valuable reference for preventing the floating of rice seedlings. Key words: floating rice seedlings; wind stress; drag force; computational fluid dynamics DOI: 10.25165/j.ijabe.20251806.9907 Citation: Li L H, Qin W H, Xu L C, Zhu C H, Liu B X. Mechanical characteristics of rice seedlings under wind stress. Int J Agric & Biol Eng, 2025; 18(6): 33–40.